A Selected Stenotaphrum secundatum as Superior Shade Tolerant Forage Resource - Juniar Sirait; Kiston Simanihuruk (Indonesian Center for Animal Research and Development, 2020)
The availability of land for forage development is limited and becomes the obstacle for supporting livestock development. One of the solutions to anticipate this problem is to utilize the lands under plantation areas by introducing shade-tolerant forage among the main crop. The area of oil palm plantations in Indonesia reaches 14,677,560 ha and is very potential to be used in the integration system with livestock. This article describes a detailed information about the superiority of selected Stenotaphrum secundatum in terms of production, nutritional quality and digestibility. Stenotaphrum secundatum is a shade tolerant forage that had derived by positive mass selection method which had been tested for its adaptability at two different elevations. The average fresh yield of S. secundatum at 55 and 75% shading level reached 2,386 and 2,001 g/m2/harvest, respectively. The digestibility of selected Steno grass on growing Boerka goat ranged from 60.7% to 72.8%. Palatability of S. secundatum grass in goats is very good with consumption reaching 3.6% of body weight. Besides being tolerant of shade, S. secundatum grass is also resistant to pests, as long as it is maintained with good management. This grass also has advantages in terms of dry matter production, nutrient content and crude protein production compared to other grass species and can be planted in wider plantation areas with 55-75% shade.